Genotoxicity and cytotoxicity analysis of curcumin and sunset yellow in human lymphocyte culture - Haverić, Anja; Haverić, Sanin; Hadžić, Maida; Lojo-Kadrić, Naida; Ibrulj, Slavka (Cellular and Molecular Biology, 2018)
Genotoxic and cytotoxic effects of curcumin and sunset yellow were tested by the chromosome aberration analysis and cytokinesis-block micronucleus cytome assay in human lymphocyte culture. Water solutions of food dyes, in concentrations of 1, 2, 4 and 8 mM, were added to the cultures at the beginning of the cultivation period. Concentrations of 4 and 8 mM of sunset yellow induced significant increase in frequencies of cells with chromosome aberrations. Tested concentrations of sunset yellow significantly associated with frequencies of structural aberrations, chromatid-type aberrations, total aberrant cells and micronuclei showing considerable dose dependent clastogenic activity. In higher analyzed concentrations, curcumin significantly increased only nuclear buds frequency, suggesting its potential genotoxicity, while sunset yellow showed dose-dependent genotoxic potential. Obtained results point toward favorization of natural coloring agents in food consumption and emphasize the need of controlled use of food colorants.